Santamaría, M.A. (2019). The Derveni Papyrus. Unearthing Ancient Mysteries - Suárez de la Torre, Emilio (ARYS. Antigüedad: Religiones y Sociedades, 2020)
SANTAMARÍA, MARCO ANTONIO (ed.) (2019). The Derveni Papyrus. Unearthing Ancient Mysteries. Papyrologica Lugduno-Batava, 36. Leiden-Boston: Brill. viii, 173 pp., 116,00€ [ISBN 978-9-0043- 8484-2] [Book review]